Gestão matricial para resultados: uma proposta de gestão da política pública de assistência social no município de Jeremoabo (Ba) - CARNEIRO, Liliane Mendes (2018)
Study of the basic aspects of the management process of public management of Social Assistance in the municipality of Jeremoabo, Bahia; The General Objective is to present a governance model based on the matrix management for results applicable to the public policy of social assistance in Jeremoabo-BA; Specific Objectives: to characterize the management of the public policy of social assistance in the municipality; to identify the aspects of the matrix management for results applicable to public social assistance policy: and to formulate a management model for results applicable to the public policy of Social Assistance of Jeremoabo). Methodology: historical study the period of 2013-2016 based on in situ research of qualitative and quantitative nature, exploratory and descriptive in which the categories used were chosen based on oral reports and interviews with managers, technicians and counselors of the municipal public policy of social assistance of the Municipality by Jeremoabo. Documentation of the area and observation of the object under study was carried out based on the comprehensivism of Max Weber. The main results found are: the phenomenon of public management and the public policy of social assistance of the municipality in question absorbed Marx Weber's "nature of rational appropriation and the conduct of the economic man"; that the Public Policy of Social Assistance in Jeremoabo (BA) has advanced, but still presents itself as centralizing, with social subjects who are not aware of SUAS, as well as there are problems of communication in the network and the system of action is not managerial; that there is a need for democratization and a more qualified and systemic management organization aiming to achieve the norms of social assistance, especially NOB-SUAS and NOB / RH-SUAS, as well as to promote Work Management in SUAS in a planning direction strategic; The data extracted makes valid, through the empiria, the hypothesis predisposed in the project that the management of the Public Policy of Social Assistance in the city of Jeremoabo (BA) can be operationalized through the matrix management of results in order to endow the management of an institutionality responsible (operational, administrative and technical-political) that guarantees the maximization of the performance of SUAS through the managerial aspects. Regarding the regulations and systematizations of the actions, it was revealed that Jeremoabo, too, is in the process of adequation in keeping with the time and historical context that belongs to him, but, it is known that the management proposed here has administrative and operative notions to the public administration of social assistance, establishing strategic knowledge and concepts in which they are designed according to a temporal, local and focused adaptation of the potentials and overcoming the obstacles predisposed to this municipal social assistance policy. We suggest, based on the research and studies so far exposed, that the matrix of results management model proposed in this work be applied in order to promote a governance structure that goes beyond procedural rites and generates a greater guarantee of rights to its users by resources, maximizing the quality of services and extending access to municipal social assistance policy.